2021
DOI: 10.1007/s00264-021-05081-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of necrotic lesion boundary in bone collapse of femoral head osteonecrosis

Abstract: Purpose Our research developed a novel approach to quantitatively evaluate the boundary of necrotic lesions in osteonecrosis of the femoral head (ONFH) and to explore its diagnostic value in predicting bone collapse of the femoral head. Methods A retrospective cross-sectional study was conducted in our institution, and 146 hips (121 cases) identified as ONFH were recruited. The anterior and lateral boundaries of each enrolled subject were measured in standard anteroposterior (AP) view and frog-leg (FL) view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…A previous study showed that the JIC class is correlated with bone collapse in ONFH. 30 Ma et al 31 reported similar results; that is, progressive necrosis and bone collapse were closely correlated with JIC classification type C2. Chen et al 32 found poorer functional results in patients with JIC classification type C2 after bone grafting compared with patients with JIC classification type C1.…”
Section: Relevant Risk Factorsmentioning
confidence: 66%
See 1 more Smart Citation
“…A previous study showed that the JIC class is correlated with bone collapse in ONFH. 30 Ma et al 31 reported similar results; that is, progressive necrosis and bone collapse were closely correlated with JIC classification type C2. Chen et al 32 found poorer functional results in patients with JIC classification type C2 after bone grafting compared with patients with JIC classification type C1.…”
Section: Relevant Risk Factorsmentioning
confidence: 66%
“…A previous study showed that the JIC class is correlated with bone collapse in ONFH 30 . Ma et al 31 .…”
Section: Discussionmentioning
confidence: 95%
“…Congratulations are this much for our awards celebration. This issue of International Orthopaedics publishes three SICOT awards papers: Diagnostic value of necrotic lesion boundary in bone collapse of femoral head osteonecrosis [14]; Jig-assisted modified Harrington reconstruction for metastatic bone destruction of the acetabulum [15]; and Sonication of explants enhancing the diagnostic accuracy of synovial fluid and tissue cultures to determine the appropriate antibiotic therapy for prosthetic joint infections [16].…”
Section: International Orthopaedics 2021 Sicot Awardsmentioning
confidence: 99%
“…With femoral head collapse as the endpoint, a Kaplan-Meier analysis was applied to calculate the femoral head's survival rate according to the necrotic zone's boundary limits. The study demonstrated that using these two parameters in plain radiography images on an antero-posterior and lateral views may contribute to better hip preservation [14]. Rajasekaran et al developed a "jig-aided technique" to improve pin placement during the Harrington technique.…”
Section: International Orthopaedics 2021 Sicot Awardsmentioning
confidence: 99%
“…4. The ARCO staging was performed on all cases according to the "2019 International Association for bone circulation research femoral head necrosis staging" [7][8][9] .…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%